FAKTOR-FAKTOR YANG MEMPENGARUHI SISWA MELANGGAR TATA TERTIB SEKOLAH DI MTs AL FALAH JATIBARU KECAMATAN BUNGARAYA KABUPATEN SIAK - Ikbal Maulana; Zahirman Zahirman; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak:This research is motivated by factors that affect students in violating the rules of school in MTs Al Falah Jatibaru Bungaraya District Siak Regency. The formulation of the problem in this researchis "what are the factors that influence students in violating the rules of school in schools in MTs Al Falah Jatibaru Bungaraya District Siak Regency ?. This study aims to analyze and describe the factors that affect students in violating the rules of school in MTs Al-Falah Jatibaru Bungaraya District Siak Regency. " This research was conducted at MTs Al-Falah Jatibaru Bungaraya on October 14-22, 2019 ". This research is quantitative descriptive. The population in this study amounted to 75 students. The sample in this study was taken from all classes. Analysis of the data of this study will conduct exploitation, describing a phenomenon that applies on the basis of data obtained in the field. Based on the results of this study indicate that there are two factors that influence students violating school rules, namely internal factors 30.28% and external, external factors that influence in this study amounted to 36.57% meaning that there are external factors that influence students violating school rules at MTsAl Falah Jatibaru Bungaraya District Siak Regency.KeyWords: Influence factors, violators of the school rules